Overview of the role of Shiga toxins in porcine edema disease pathogenesis - Casanova, Natalia Andrea; Redondo, Leandro Martin; Dailoff, Gabriela Cecilia; Arenas, David; Fernandez Miyakawa, Mariano Enrique (Elsevier, 2024)
Shiga toxin-producing Escherichia coli (STEC) have been implicated as the cause of enterotoxemias, such as hemolytic uremic syndrome in humans and edema disease (ED) of pigs. Stx1 and Stx2 are the most common types found in association with illness, but only Stx2e is associated with disease in the animal host. Porcine edema disease is a serious affection which can lead to dead causing great losses of weaned piglets. Stx2e is the most frequent Stx variant found in porcine feces and is considered the key virulence factor involved in the pathogenesis of porcine edema disease. Stx2e binds with higher affinity to Gb4 receptor than to Gb3 which could be due to amino acid changes in B subunit. Moreover, this subtype also binds to Forssman glycosphingolipids conferring upon Stx2e a unique promiscuous recognition feature. Manifestations of edema disease are caused by systemic effects of Stx2e with no significant morphologic changes in enterocytes. Endothelial cell necrosis in the brain is an early event in the pathogenesis of ED caused by Stx2e-producing STEC strains. Further studies are needed to generate techniques and tools which allow to understand the circulation and ecology of STEC strains in pigs even in resistant animals for diagnostic and epidemiological purposes.